CAPACITY BUILDING: GOVERNANCE PERSPECTIVE ON WASTE MANAGEMENT UNIT IN SRAGEN BUNDER MARKET - Kristina Setyowati; Didik Gunawan; Faizatul Ansoriyah (Universitas Sebelas Maret, 2015)
Public waste has become national problems. As part of solving the problem the management of public waste needs to be comprehensive and integrated so the processed public waste able to provide economic benefits, healthy for people, safe for the environment and not to forget also able to change people's behavior. Governance perspective is involving three pillars: government, private and citizens. In this study this parties were represented by Sragen Regency Government as government, Danamon Peduli Foundation as private and small scale vendors as citizens. All of which were expected to bring effectiveness in empowering waste management unit. Partnership and capacity building are expected to strengthen the knowledge as well as managerial capability and capacity in the traditional market waste management. This article aims to describe the waste management with governance perspectibe in Bunder traditional market, Sragen, Indonesia. Keyword: Empowerment, Capacity building, Governance